Sink or swim - Katschke, Judy (New York : Scholastic, 2018)
Ms. Frizzle takes the class on a trip to Hawaii, where the Magic School Bus provides them with individual submarines, and they learn about fish schools and the behavior of undersea animals--and try to avoid being eaten by a shark.
"Based on the television series The Magic School Bus: Rides Again"--Title page verso.
"Based on the Magic School Bus series [created by] Joanna Cole and Bruce Degen."
540L
Decoding demand: 88 (very high) Semantic demand: 96 (very high) Syntactic demand: 79 (high) Structure demand: 84 (very high)
Accelerated Reader AR
Keywords: Frizzle, Ms. (Fictitious character) -- Juvenile fiction; Teachers -- Juvenile fiction; School field trips -- Juvenile fiction; Sharks -- Behavior; Fishes -- Behavior; Marine animals -- Juvenile fiction; Frizzle, Ms. (Fictitious character) -- Fiction; Teachers -- Fiction; School field trips -- Fiction; Fishes -- Fiction; Sharks -- Fiction; Hawaii -- Juvenile fiction; Hawaii -- Fiction